Effect of biannual azithromycin on respiratory pathogens among symptomatic children: results from the randomised Macrolides Oraux pour Réduire les Décès avec un Oeil sur la Résistance (MORDOR) I trial - Jie Liu; Thomas M Lietman; Jeremy D Keenan; Kieran S O'Brien; Elodie Lebas; Amza Abdou; Benjamin F Arnold; James A Platts-Mills; Eric R Houpt; Stephanie A Brennhofer; Elizabeth T Rogawski McQuade; Ramatou Maliki; et al. (BMJ Global Health)
Introduction Biannual (ie, every 6 months) mass drug administration of azithromycin has reduced childhood mortality in Niger, but its effects on specific respiratory pathogens are not fully elucidated.Methods Across 2 years of the Macrolides Oraux pour Réduire les Décès avec un Oeil sur la Résistance (MORDOR) study in Niger, we evaluated 1468 nasopharyngeal swabs from children who presented for care with respiratory symptoms. Swabs were tested by quantitative PCR using a customised TaqMan Array Card that included assays for 19 respiratory pathogens.Results Nasopharyngeal detection of Haemophilus influenzae, Moraxella catarrhalis and Streptococcus pneumoniae was common in both azithromycin and placebo communities. The prevalence was reduced in children from azithromycin communities for just two pathogens: Bordetella pertussis and H. influenzae type b (Hib). These children had a 49% and 65% reduction in the prevalence of B. pertussis and Hib in nasopharyngeal swabs, respectively, compared with children from the control communities (prevalence ratios 0.51, 95% CI 0.35, 0.75; and 0.35, 95% CI 0.17, 0.71).Conclusions Biannual administration of azithromycin to communities in Niger was associated with lower prevalence of B. pertussis and Hib compared with placebo. These reductions may explain some of the childhood mortality benefit of azithromycin.Trial registration number NCT02048007.